History, current trends and prospects for the development of pro- and prebiotic drugs in Russia and abroad - Yu. S. Savinova; N. L. Belkova; N. V. Semenova; L. V. Rychkova (Acta Biomedica Scientifica)
The gut microbiota is the largest human microbial community, comprising more than 1000 species of various microorganisms. It has been established that these are the gut microorganisms that play a decisive role in maintaining health, participating in the metabolism of proteins, carbohydrates, lipids, bile acids and the synthesis of vitamins. It has been shown that changes in the balance in the gut microbiocenosis lead not only to pathologies of the gastrointestinal tract, but also increase the risk of developing diseases of the cardiovascular and endocrine systems, and cause disturbances in the psycho-emotional state.   To restore, correct and maintain the gut microbiota, probiotic preparations are recommended. In connection with the obvious relevance of the use of probiotics, this review aimed to describe the history of the emergence of the first probiotic products, current trends in the development of the concept of functional foods enriched with probiotics, as well as the prospects for developing probiotic preparations in the Russian Federation and abroad.   This article presents an analysis of the market for probiotic preparations and dietary supplements, as well as functional food products that are produced in the Siberian Federal District. For an objective assessment of the development of the market for probiotic products, a generalization of analytical data from marketing services that monitor the movement of medicines in pharmacy chains and analyze consumer reviews was carried out.